The Analisis dan Perancangan Toko Online Berbasis Web Pada Tanaman Mini Yogyakarta - Nurdianah, Siti; Hariyanto, Bagus; Haeri, Boby Renvi; Khotimah, Siti (TIN: Terapan Informatika Nusantara, 2021)
Tanaman Mini is a place for ornamental plant cultivation located in Denokan Hamlet, Sleman - Jogjakarta, mini plants sell various types of ornamental plants, liquid organic fertilizer, rabbit urine fertilizer, fertilizer for varigata, medicinal plants such as pesticides. In addition, mini plants sell planting media, there are 2 types of planting media, namely allocative planting media and planting media for varigata plants. As well as selling Moss (moss) and there are 2 types of Moss, namely Moss premium and Moss regular. However, Tanaman Mini are currently in product sales transactions using social media and the ordering process is written in a ledger so it is very difficult to make stock reports & sales reports .. To solve the existing problems, the Tanaman Mini shop wants to build an online sales system (E-Commerce) as a website to sell products sold by the Mini Plant shop and computerized sales transactions. to exist in the business world. With information system technology, it will facilitate various activities of delivering information or managing data in E-commerce. This research aims to facilitate service to consumers. by using a website-based information system and being able to present detailed information on plant species, finding information on seed types becomes easier. This system is designed using the PHP programming language and MySQL database